ETIKA PERTANGGUNGJAWABAN LINGKUNGAN DALAM BINGKAI AL-QUR’AN - Saadah, Naili; Farida, Dessy Noor (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2019)
Environmental responsibility (ER) is a topic that is often discussed lately. This is because the ecological crisis is increasingly alarming. massive natural exploration by the company as if not paying attention to the damage caused. land clearing, mining of natural energy sources and pollution are examples of activities that contribute to the destruction of nature. The problem of environmental damage today is no longer a problem that is separate from religion because, in reality, the destruction of nature is a result of the spiritual crisis of modern humans which causes greed. Departing from these conditions, this study questions how the ethics of environmental responsibility in the rules of Qur'an. Using a sample of companies registered with the Jakarta Islamic Index, this study seeks to explore facts based on the annual reports reported by the company. This research found an alarming fact, where there are still many companies registered in the Jakarta Islamic Index that have not fulfilled the ethics of environmental accountability as regulated in the Qur'an.